Towards Logical Clocks in P2P-based MMVEs - Weis, Torben; Wacker, Arno; Schuster, Sebastian; Holzapfel, Sebastian (Electronic Communications of the EASST, 2009)
A crucial requirement for peer-to-peer-based Massively Multiuser VirtualEnvironments (P2P-based MMVEs) is the accurate and reliable synchronization ofactions among the users (processes). To do so, clock synchronization protocolscan be used. In this paper we first analyze the usage of standard vector clocks forthis purpose and show their deficits (e.g. growing large). Then we present a novelvariation of vector clocks – pruned vector clocks – which overcome the deficits ofstandard vector clocks and are therefore suited for their usage in MMVEs. The basicidea of pruned vector clocks is to prune all entries in a vector clock, which are notrelevant at some point in time. We show, that with this approach vector clocks willstay constant in size and still provide the necessarily synchronization among theprocesses.